Bacterial nanocellulose spheres coated with meta acrylic copolymer: Vaccinium meridionale swartz extract delivery for colorectal cancer chemoprevention (2024)
ABSTRACT: Bacterial nanocellulose, a natural hydrocolloid traditionally used as food ingredient, has demonstrated potential as a non-soluble dietary fiber and functional material. Moreover, its properties can further be potentialized whether coupled with natural anthocyanins to endow antioxidant activity. Vaccinium meridionale swartz extract (VE), rich in anthocyanins, has recently demonstrated effects against colorectal cancer; therefore, encapsulating it into bacterial nanocellulose (BNC) may offer an enhanced VE delivery alternative. However, BNC has an open interconnected porosity that may generate a quick delivery of VE in gastric fluids impacting its stability. Accordingly, this paper explores meta-acrylic copolymer coatings of BNC spheres for VE delivery in a colorectal environment while potentially reducing its delivery in stomach conditions. The VE was characterized in terms of antioxidant capacity, colorectal cancer cell inhibition, and selectivity and then, it was incorporated into BNC spheres and coated with a meta-acrylic copolymer. The system’s physicochemical, morphological, and delivery performance was studied under colonic and gastric conditions. Results show the coating’s effectiveness in changing the VE delivery profile under colonic conditions and the potential of natural extracts for the selective inhibition of colorectal cancer cells (SW480 and SW620). The above results demonstrated that meta-acrylic copolymer-coated BNC spheres is a potential system for encapsulating natural extracts for colorectal cancer chemoprevention.